Alasan Warga Daerah Agraris Menjalankan Bisnis - Kurniawan, Aries; Farida, Yuni Nur (Jurnal Riset Entrepreneurship, 2019)
ABSTRACTThis study aims to find out the reasons or basis of why they choose to run a business or become entrepreneurs in the majority of the community as fish farmers and employees. This study uses qualitative methods with the determination of samples using incidental methods.The results of the study show that the reasons for the villagers to carry out entrepreneurial activities are influenced by two factors, namely internal factors and external factors. Internal factors are factors that arise from within yourself. While external factors are factors that arise from outside that cannot be controlled.This internal factor is divided into two, namely because of intent and accident. Deliberation is caused by intentions from within while accidental is usually caused by requests from outside. While external factors are more caused by termination of employment or other things that cause a person to be unable to continue working. About how to manage a business, it is generally done in a simple and manual manner. Their most important principle is that the business goes without any significant obstacles.